Leadership Style and Employees’ Productivity: Evidenced from Nigerian Banking Sector - Olanrewaju, Salami Akeem; Alhaji, Salau Abdulazeez; Okpara, Kyrian Kelechi; Abdulraheem, Issa (NIU Journal of Humanities, 2020)
The study focused on leadership style and employees’ productivity evidenced from banking sector in Nigeria. The banking sector had been globally acknowledged as a pivot to the economic growth of any country. The study used questionnaires to elicit information from 80 staff of different banks in Ilorin metropolis through a simple random sampling technique. The data were analyzed using descriptive and inferential statistics. 94.12% acknowledged participatory as the most used leadership style in banking sector. Two hypotheses were tested. The result of hypothesis one shows that there is significant positive correlation between leadership styles (participatory and charismatic) and employees’ productivity variables. That is r = 0.638 for effectiveness variable in participatory leadership style and r = 0.369 and 0.596 for efficiency and commitment in charismatic leadership style. The result of hypothesis two shows r 2 = 0.825, which implies that about 82.5% of the variation in leadership style is explained by the variables in the model. The study thus recommends that participatory and charismatic leadership styles should be encouraged fully in the banking industry, so as to boost employees’ commitment. Keywords : Leadership style, Employee productivity, Banking sector, Performance